96.5k views
5 votes
Solve this equation. 12 - 3x = 4+ (-2x)​

2 Answers

5 votes

Answer:

x=8

Explanation:

12 -3x=4+ (-2x)

12-3x=4-2x add 12 to both sides

-3x=-2x-8 add 2x to both sides

-x=-8 divide both sides by 1

x=8

let me know if this helped :)

User Alexis Coles
by
7.9k points
7 votes

Answer: -2x = 16

Explanation:

The answer is -2x = 16.

We start by isolating the -2x on one side of the equation. To do this, we must subtract 3x from both sides of the equation. This gives us -2x = 4 - 3x. We then add 3x to both sides of the equation to give us -2x + 3x = 4. Since 3x + (-3x) = 0, we are left with -2x = 16.

User Siew
by
7.8k points